Pengaruh KOMARASCA (Kompos-Arang Aktif-Asap Cair) Dari Hasil Pengolahan Sampah Organik Pada Pertumbuhan Tanaman Gynura pseudochna (Lour) DC - Haji, Abdul Gani (Universitas Syiah Kuala, 2010)
This study aims to determine the effect of komarasca (compost-activated carbon, liquid smoke) results of processing solid organic waste on plant growth god leaves (Gynura pseudochna (Lour) DC). Solid organic waste comes from the market in Bogor City consisting of leaves, wood, bamboo, and twigs of plants. Compost is made by waste composting techniques biodekomposer type leaves using Effective Microorganism (EM-4), whereas activated charcoal and liquid smoke is made through the pyrolysis process of solid waste mixture consisting of 50% wood, 25% bamboo and 25% twigs of plants. Seedling leaf plant using is the god of tuber crops from the Garden Study Center medicinal Cikabayang IPB, Bogor. Tuber is cut into pieces measuring 1.5 to 2.0 cm, and then sowing to grow and produce leaves 2-3. Planting medium used a mixture of soil-compost-activated carbon treatment made by certain variations and each is inserted into the plastic polyback. God leaf seedlings planted simultaneously in poliback was completed, the planting medium. Observation the growth of plants includes the amount of leaf, stem height and number of tillers. After a 30-day-old plants sprayed with pesticides. The observation on days 0, 10, 20, and 30 showed an increase in the number of leaves, stem height and number of tillers. The observation after the plants sprayed with liquid smoke showed good plant growth the number of leaves, stem height and number of tillers is increasing especially in the treatment of M5P1 (addition of activated carbon with steam activation results and liquid smoke).